The Effects of Cornus mas Hydro-Methanolic Extract on Cisplatin-Induced Nephrotoxicity in Rats - Atefe Mohammadzadeh Vardin; Monireh Khordadmehr; Reza Heidari; Hedaiat-; Maryam Bannazadeh Amirkhiz; Mehran Mesgari Abbasi (Tabriz University of Medical Sciences, 2018)
Background: Cisplatin (Cis) is a chemotherapeutic agent and nephrotoxicity is a serious adverse effect of the drug. This study investigated the protective effects of Cornus mas fruit hydro-methanolic extract (CME) on cisplatin-induced nephrotoxicity in a rat model. Methods: Forty Wistar rats were divided into the control group, CME group, CME 300 + Cis group, CME 700 + Cis group, and Cis group. After the intervention samples were taken for biochemical and histopathological analysis. Results: The CME analysis showed considerable total antioxidant and total phenol contents. The blood serum urea and creatinine increased (p < 0.01) in the Cis group rats. In the Cis + CME groups, the parameters were not significantly different from that of the control group. There were no significant differences in the renal activities of SOD, GPx, CAT, and TAC between the Cis-treated and control groups (p > 0.05). The renal MDA levels of the Cis and CME 300 + Cis groups decreased significantly in comparison to the control and the CME groups (p < 0.01 and p < 0.05, respectively). In the histopathological examination, mild to severe degeneration was observed in the Cis group. Despite the presence of mild degeneration, they were less severe in the Cis + CME groups, and maintained a better morphology when compared to the Cis group (p < 0.01). Conclusion: The results showed renoprotective effects of CME against Cis-induced nephrotoxicity in rats.